\(\frac{-3}{7}+\frac{15}{26}-\left(\frac{2}{13}-\frac{3}{7}\right)\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\frac{-3}{7}+\frac{15}{26}-\left(\frac{2}{13}-\frac{3}{7}\right)=\frac{-3}{7}+\frac{15}{26}-\frac{2}{13}+\frac{3}{7}=\left(\frac{-3}{7}+\frac{3}{7}\right)+\left(\frac{15}{26}-\frac{2}{13}\right)\)
\(=\frac{15-4}{26}=\frac{11}{26}\)
c) \(\frac{-11}{23}.\frac{6}{7}+\frac{8}{7}.\frac{-11}{23}-\frac{1}{23}=\frac{-11}{23}.\left(\frac{6}{7}+\frac{8}{7}\right)-\frac{1}{23}\)
\(=\frac{-11}{23}.2-\frac{1}{23}=\frac{-22-1}{23}=\frac{-23}{23}=-1\)
a. \(\frac{-3}{7}+\frac{15}{26}-\left(\frac{2}{13}-\frac{3}{7}\right)=\frac{-3}{7}+\frac{15}{26}-\frac{2}{13}+\frac{3}{7}=\frac{15}{13.2}-\frac{2}{13}=\frac{15}{13.2}-\frac{2.2}{13.2}=\frac{15-4}{26}=\frac{11}{26}\)
C. \(\frac{-11}{23}.\frac{6}{7}+\frac{8}{7}.\frac{-11}{23}-\frac{1}{23}=\frac{1}{23}.\left(-11.\frac{6}{7}-11.\frac{8}{7}-1\right)=\frac{1}{23}.\left(-22-1\right)=\frac{1}{23}.\left(-23\right)=-1\)
\(=\frac{6}{7}:\frac{-2}{26}+\frac{6}{7}:\frac{-3}{2}=\frac{-78}{7}+\frac{-4}{7}=\frac{-82}{7}\)
=\(\frac{6}{7}:\left(\frac{3}{26}_{ }-\frac{6}{26}\right)+\frac{6}{7}:\left(\frac{1}{10}-\frac{16}{10}\right)\)
=\(\frac{6}{7}:\frac{-3}{26}+\frac{6}{7}:\frac{-3}{10}\)
=\(\frac{6}{7}.\frac{-26}{3}+\frac{6}{7}.\frac{-10}{3}\)
=\(\frac{6}{7}.\left(\frac{-26}{3}+\frac{-10}{3}\right)\)
=\(\frac{6}{7}.\left(-12\right)\)
=\(\frac{-72}{7}=-10\frac{2}{7}\)
2: \(=\dfrac{0.8}{\dfrac{16}{25}-\dfrac{1}{25}}+\dfrac{\dfrac{71}{75}\cdot\dfrac{7}{4}}{\dfrac{119}{36}\cdot\dfrac{36}{17}}\)
\(=\dfrac{4}{5}\cdot\dfrac{5}{3}+\dfrac{71}{300}=\dfrac{471}{300}=\dfrac{157}{100}\)
3: \(=\dfrac{\dfrac{2}{5}-\dfrac{2}{9}+\dfrac{2}{11}}{\dfrac{7}{5}-\dfrac{7}{9}+\dfrac{7}{11}}-\dfrac{\dfrac{2}{6}-\dfrac{2}{8}+\dfrac{2}{10}}{\dfrac{7}{6}-\dfrac{7}{8}+\dfrac{7}{10}}\)
=2/7-2/7=0
\(-\frac{3}{7}+\frac{15}{26}-\left(\frac{2}{13}-\frac{3}{7}\right)\)
\(=-\frac{3}{7}+\frac{15}{26}-\frac{2}{13}+\frac{3}{7}\)
\(=\left(-\frac{3}{7}+\frac{3}{7}\right)+\left(\frac{15}{26}-\frac{2}{13}\right)\)
\(=\left(-\frac{3}{7}+\frac{3}{7}\right)+\left(\frac{15}{26}-\frac{4}{26}\right)\)
\(=0+\frac{11}{26}\)
\(\Rightarrow=\frac{11}{26}\)
Tích nha
11/26 ban a